2019
DOI: 10.1186/s40169-019-0234-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical applications of fucoidan in translational medicine for adjuvant cancer therapy

Abstract: The chemical composition of fucoidan, a kind of sulfated polysaccharide mainly derived from brown seaweed, includes a substantial percentage of l -fucose. Fucoidan has various biological and pharmacological activities, such as anti-cancer/anti-tumor, anti-proliferation, anti-inflammatory and immune-modulatory functions, and fucoidan-related dietary supplements and nutraceuticals have recently drawn considerable attention. In this review, we aim to provide a current view of different aspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
83
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(91 citation statements)
references
References 97 publications
(151 reference statements)
2
83
0
6
Order By: Relevance
“…Several 2019 reviews reveal fucoidans (sulfated polysaccharide mainly derived from brown seaweed) in lung cancer management. Brown algae like Fucus vesiculosus, Turbinaria conoides, Laminaria japonica ( Figure 8) are reported in inhibition of tumor migration and invasion, apoptosis induction and inhibition lung cancer cell progression respectively [159]. Fucus evanescens, Sargassum sp.…”
Section: Cancer Prevention and Tumor Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…Several 2019 reviews reveal fucoidans (sulfated polysaccharide mainly derived from brown seaweed) in lung cancer management. Brown algae like Fucus vesiculosus, Turbinaria conoides, Laminaria japonica ( Figure 8) are reported in inhibition of tumor migration and invasion, apoptosis induction and inhibition lung cancer cell progression respectively [159]. Fucus evanescens, Sargassum sp.…”
Section: Cancer Prevention and Tumor Controlmentioning
confidence: 99%
“…Jazzara et al [170] concluded that λ-carrageenan (sulfated galactans found in certain red seaweeds) could be a promising bioactive polymer, showed a remarkable inhibitory effect on MDA-MB-231(triple negative breast cancer cell line) cell migration [171]. Several studies support polyphenols [172][173][174][175][176], flavonoids [177][178][179][180][181][182][183][184][185][186], fucoidan [159,160,166,[187][188][189][190][191][192][193][194][195], lutein/zeaxanthin [196][197][198][199][200], other seaweed alkaloids, peptides, tannins and polysaccharides [132,164,[201][202][203][204][205][206][207][208][209][210] in breast cancer management. The number of deaths from colorectal cancer in Japan continues to increase [211], it is the third most common diagnosis and second deadliest malignancy for both sexes combined…”
Section: Cancer Prevention and Tumor Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Основным полисахаридом в составе бурых водорослей является фукоидан [42]. В исследованиях in vitro и in vivo на мышах обнаружены иммуномодулирующие, антибактериальные, противовирусные, противовоспалительные и противоопухолевые свойства фукоидана [42][43][44]. В исследованиях на мышах показано, что фукоидан способствует созреванию дендритных клеток [45].…”
Section: обзор литературыunclassified
“…In the last few years, macroalgae attracted increasing attention from many industries of diverse branches such as fuel, plastics, cosmetics, pharmaceuticals, and food [1,2]. In fact, the chemical diversity within red (Rhodophyta), green (Chlorophyta), and brown (Phaeophyta) macroalgae offers the possibility of finding a wide variety of primary and secondary metabolites, with interesting properties and applications [1,[3][4][5][6][7]. Primary metabolites are directly involved in physiological functions, under normal growth conditions, such as reproduction, while secondary metabolites are mainly excretory products produced under different stress conditions, such as exposure to ultraviolet (UV) radiation, changes in temperature and salinity, or environmental pollutants.…”
Section: Introductionmentioning
confidence: 99%